Laparoscopic management of gastric liposarcoma: A case report and review of the literature. (2020) - Cure, Hector W.; Gómez, Daniel; Pedraza, Mauricio; Bulicie, Hector Cure; Cabrera, Luis Felipe; Gil, Luis Paolo Gil; Acevedo, David; Cabrera, Laura; Moreno, Valery; Mendoza, Andrés
Highlights: Soft tissue tumors are characterized by frequent somatic chromosomal rearrangements. Symptoms include epigastric pain, nausea, anorexia, and gastrointestinal bleeding. Gastric liposarcoma is the least common sarcoma of the gastrointestinal tract. CT and pathological analysis of resected specimens enable diagnosis. The gold standard of treatment is surgery with radical resection of the tumor. Abstract: Introduction: Liposarcoma is one of the most common mesenchymal neoplasms in adults. Predominant locations are the retroperitoneum and limbs, it rarely occurs in the gastrointestinal tract. Gastric liposarcoma is extremely rare, with fewer than 30 cases reported around the world. Presentation of case: Here we present the case of a 70-year-old female patient who was diagnosed with gastric liposarcoma and managed with laparoscopic surgical resection. The patient is currently being followed up and is alive without recurrence 12 months after the operation. Discussion: Gastric liposarcoma approach requires proper diagnosis with computed tomography and endoscopy, in order to develop an adequate surgical plan. Laparoscopic en-bloc resection and gastrointestinal reconstruction is the ideal management in this type of patient. Conclusion: Gastric liposarcoma is an extremely rare entity, his management consists of wide en-bloc resection with a gastrointestinal reconstruction.